Viscosity of nanofluids: A review of recent experimental studies - Bashirnezhad, K.; Bazri, S.; Safaei, M.R.; Goodarzi, M.; Dahari, M.; Mahian, O.; Dalkiliça, A.S.; Wongwises, S. (Elsevier, 2016)
During the past decade, nanotechnology with its rapid development has grabbed the attention of scientists, scholars, and engineers. Nanofluids are one of the surprising outcomes of this technology that could increase the efficiency of thermal systems remarkably. Nanofluids containing solid nanoparticles have a higher viscosity than common working fluids; hence, measuring the viscosity is necessary for designing thermal systems and estimating the required pumping power. In the current review study, an attempt has been made to cover the latest experimental studies performed on the viscosity of nanofluids. An experimental investigation is very vital for the analysis since the theoretical models usually underestimate the nanofluid viscosity. Through experiments, the real effects of volume fraction, temperature, particle size, and shape on the viscosity of nanofluids will be determined.